PENGEMBANGAN MEDIA BUKU SAKU EDUKATIF SEBAGAI MEDIA PEMBELAJARAN MASYARAKAT DALAM PENGELOLAAN LIMBAH PRODUKSI RUMAH KAYU DI DESA TANJUNG BATU SEBERANG - Mayang Bunga Kurnia; Ardi Saputra; Erna Retna Safitri; Shomedran (STKIP Subang, 2026)
This study aims to develop an educational pocketbook as a community learning medium for managing wood house production waste in Tanjung Batu Seberang village and to determine its validity and practically. The method used in this study was Research and Development (R&D) with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects included the community of Tanjung Batu Seberang village who work as wood house craftsmen and expert validators. Data were collected through validation questionnaires and user response questionnaires, which were analyzed using a rating scale. The validation results showed that the developed pocketbook achieved a very good level of validity in terms of material (83%), media (93%), and language (95%). The practicality test results at the one to one and small group stages showed a percentage of 100%, categorized as very practical. The educational pocketbook was considered easy to use, attractive, and effective in improving community understanding of managing and utilizing wood house production waste. Therefore, the developed educational pocketbook is feasible to be used as a community learning medium.